Evaluation of the Factors Affecting Survival in Patients with Gastric Cancer According to the 8th Edition of the Tumor, Node and Metastasis Classification - Mustafa Berkeşoğlu; Recep Çağlar; Aydemir Ölmez; Hakan Canbaz; Bahar Taşdelen; Mustafa Musa Dirlik; Tuba Kara (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:We aimed to evaluate the effect of different parameters on survival in patients with gastric adenocarcinoma who underwent D2 lymph node dissection with more than 15 lymph nodes.Methods:A total of 161 patients with gastric adenocarcinoma, who underwent curative gastrectomy and had more than 15 lymph nodes dissected between January 2001 and January 2015, were retrospectively evaluated. A hundred and forty-six patients were included in the study.Results:The mean follow-up period was 24 (12-102) months and the mean survival time was 818.80±692.42 (66-3065) days. Gender, age, lymphovascular invasion and perineural invasion, tumor differentiation and histology were not found to have a statistically significant effect on overall survival. Length of hospital stay, tumor location, extent of surgery, chemotherapy, tumor stage (T category), total number of harvested lymph nodes, number of metastatic lymph nodes, lymph node status (N status), percentage of lymph node positivity, metastatic lymph node ratio and stage were found to have a statistically significant effect on overall survival.Conclusion:Having distally located tumor, having chemotherapy, higher total number of harvested lymph node and lower N category were better prognostic factor for overall survival in gastric cancer patients having curative resection with more than 15 lymph nodes harvested.